Politics of Climate Change: A Comparative Study of the Chinese and the US Responses - Amjid Rana; Saima Gul (ASIAN Journal of International Peace & Security (AJIPS), 2023)
The climate change has menacingly threatened the environmental system due to emission of greenhouse gasses. On the other hand, the world’s economic infrastructure mostly has a carbon economy that could collapse if carbon footprint is suddenly reduced. Due to the inverse relationship between economic interests and climate change, states are not taking climate catastrophe seriously. Countries like China and the US, with significant footprints of carbon in the world, have manipulated and abandoned the climate objectives for economic pursuits. Their responses towards climate change are often driven by their narrowly conceived economic and political objectives, hindering their compliance and cooperation to tackle climate change. The study suggests two points: the US and China will keep relying on fossil fuels for economic objectives, and climate politics between these two countries and unwillingness on their part to share the burden have threatened both states’ climate obligations. Hence, climate change can betackled proficiently if the US and China cooperate by enhancing trust on each other tofight climate change and shift their industries and manufacturing sectors to clean energy instead of fossil fuels.